2021
DOI: 10.3390/metabo11100650
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Possible Salivary Metabolic Biomarkers and Altered Metabolic Pathways in South American Patients Diagnosed with Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) represents 90% of oral malignant neoplasms. The search for specific biomarkers for OSCC is a very active field of research contributing to establishing early diagnostic methods and unraveling underlying pathogenic mechanisms. In this work we investigated the salivary metabolites and the metabolic pathways of OSCC aiming find possible biomarkers. Salivary metabolites samples from 27 OSCC patients and 41 control individuals were compared through a gas chromatography coupled to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…Several studies, with different protocols, conducted over the last few years identified different saliva metabolite concentrations either between healthy controls and oral squamous cell carcinoma subjects or between OSCC subjects and premalignant lesion subjects (oral lichen planus, oral leukoplakia, precancerous dysplasia, keratosis). Their samples, analytical and discrimination methods and outcomes are summarized in Table 1 [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. A notable diversity of candidate biomarkers is presented in these studies.…”
Section: The Human Salivary Metabolome and Oral Pathologiesmentioning
confidence: 99%
“…Several studies, with different protocols, conducted over the last few years identified different saliva metabolite concentrations either between healthy controls and oral squamous cell carcinoma subjects or between OSCC subjects and premalignant lesion subjects (oral lichen planus, oral leukoplakia, precancerous dysplasia, keratosis). Their samples, analytical and discrimination methods and outcomes are summarized in Table 1 [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. A notable diversity of candidate biomarkers is presented in these studies.…”
Section: The Human Salivary Metabolome and Oral Pathologiesmentioning
confidence: 99%
“…Metabolites are small molecules that are involved in the body's metabolic processes, including the breakdown and synthesis of nutrients and other molecules. The metabolic analysis of saliva involves the identification and quantification of specific metabolites in saliva samples 93 . Salivary biomarkers have been studied as potential indicators of metabolic disorders such as diabetes and obesity.…”
Section: The Nature Of Salivamentioning
confidence: 99%
“…Univariate analyses were used to quantify 25 hydrophilic metabolites, such as choline and urea, and revealed a substantial difference between OSCC and HC samples. Gas chromatography-MS (GC-MS) was used to analyze OSCC and HC saliva samples obtained from a South American population [ 22 ]. The results of receiver operating characteristic analysis identified 24 metabolites, such as malic acid, maltose, methionine, and inosine, for distinguishing between patients with OSCC and HCs.…”
Section: Applications For Cancer Biomarker Discoverymentioning
confidence: 99%
“…It consumes a small volume of samples and enables the identification and quantification of hundreds of metabolites simultaneously [ 53 ]. However, direct injection to MS cannot separate the metabolites with the same m/z (mass divided by charge number) value, such as leucine and isoleucine; therefore, a separation system is usually used before MS. GC-MS allows the quantification volatile compounds and the profiling of non-volatile metabolites by derivatization, which was used to analyze OSCC samples [ 22 ]. Liquid chromatography (LC)-MS has been used for both non-targeted and targeted analyses of salivary metabolites.…”
Section: Technical Challenges In Salivary Metabolomic Studiesmentioning
confidence: 99%